2020
DOI: 10.1029/2020gl089137
|View full text |Cite
|
Sign up to set email alerts
|

Routes of the Upper Branch of the Atlantic Meridional Overturning Circulation according to an Ocean State Estimate

Abstract: The origins of the upper branch of the Atlantic meridional overturning circulation (AMOC) are traced with backward-in-time Lagrangian trajectories, quantifying the partition of volume transport between different routes of entry from the Indo-Pacific into the Atlantic. Particles are advected by the velocity field from a recent release of "Estimating the Circulation and Climate of the Ocean" (ECCOv4). This global time-variable velocity field is a dynamically consistent interpolation of over 1 billion oceanograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
(88 reference statements)
1
24
1
Order By: Relevance
“…The TL can be readily identified in salinity profiles around Australia (Figures 1 and S2; Table S1). TL flow is ∼4 Sv in both modeling (van Sebille et al, 2012) and float (Rosell-Fieschi et al, 2013) studies, compared to 14.3 Sv through the ITF (van Sebille et al, 2014), whereas more recent modeling suggests a somewhat greater role for TL (Rousselet et al, 2020). TL flow varies seasonally (Rosell-Fieschi et al, 2013;van Sebille et al, 2012) and largely depends on large-scale wind patterns over the Pacific (van Sebille et al, 2014).…”
Section: Modern Tasman Leakage and The Southern Hemisphere Supergyrementioning
confidence: 87%
See 1 more Smart Citation
“…The TL can be readily identified in salinity profiles around Australia (Figures 1 and S2; Table S1). TL flow is ∼4 Sv in both modeling (van Sebille et al, 2012) and float (Rosell-Fieschi et al, 2013) studies, compared to 14.3 Sv through the ITF (van Sebille et al, 2014), whereas more recent modeling suggests a somewhat greater role for TL (Rousselet et al, 2020). TL flow varies seasonally (Rosell-Fieschi et al, 2013;van Sebille et al, 2012) and largely depends on large-scale wind patterns over the Pacific (van Sebille et al, 2014).…”
Section: Modern Tasman Leakage and The Southern Hemisphere Supergyrementioning
confidence: 87%
“…The reality, however, is more complex (e.g., , with the Indian Ocean increasingly seen as playing a more critical role in thermohaline circulation (Schott et al, 2009). It is now clear that both the ITF and TL are important inter-basinal connections that ultimately provide return waters for the North Atlantic through the Agulhas Current (Durgadoo et al, 2017;Rousselet et al, 2020). Flow through both the Tasman and Agulhas Leakages has been increasing over the past decades (Qu et al, 2019; Figure 1).…”
Section: Tasman Leakage Importance In the Global Thermohaline Circulationmentioning
confidence: 99%
“…IndividualDisplacements.jl is most directly related to the MITgcm/flt Fortran package which the author also recently extended (Campin et al, 2020). This new Julia package was in fact partly motivated by a need to provide an easier and simpler alternative to using MITgcm/flt in its offline mode in order to handle global grids not readily supported by other packages (G. Forget et al, 2015;Gaël Forget, 2020;Rousselet et al, 2020).…”
Section: Statement Of Needmentioning
confidence: 99%
“…At this stage, IndividualDisplacements.jl is considered production-ready, such that we could immediately start transferring several ongoing research collaborations that use MITgcm and ECCO (Gaël Forget & Ferreira, 2019;Rousselet et al, 2020) from Fortran to Julia. Extension to other models may start with MERRA2 / MITgcm coupled model runs (Strobach et al, 2020) and near-term applications could also include data assimilation to better simulate plastic garbage patches (Peytavin et al, 2021).…”
Section: Statement Of Needmentioning
confidence: 99%
“…However, later observational studies suggested that deep waters, including PDW, mainly return to the surface via along‐isopycnal pathways in the Southern Ocean (e.g., Marshall & Speer, 2012). In this paradigm, the ITF is relegated to a component of the circum‐Australia circulation with a small role in the global overturning circulation (Rousselet et al, 2020; Sloyan & Rintoul, 2001). Thus, most studies of ITF transport variability have focused on local processes in the Indo‐Pacific Basin (e.g., Feng et al, 2018; Godfrey, 1996; Sprintall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%